2013
DOI: 10.1155/2013/630723
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Revealing Pharmacological Signalling Pathway Networks in the Hippocampus of Ischaemia-Reperfusion Mice Treated with Baicalin

Abstract: Background. Baicalin (BA) exhibits ill understood neuroprotective, anti-inflammatory, and antioxidative effects in brain injury. Objective. To identify the differential network pathways associated with BA-related biological effects. Methods. MCAO-induced mice received BA 5 mg/Kg (BA group). Controls received vehicle only. Following ischaemia-reperfusion, ArrayTrack analysed the whole genome microarray of hippocampal genes, and MetaCore analysed differentially expressed genes. Results. Four reversing pathways w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Baicalin activation of the cyclinD-SMAD3-TGF beta network pathway may improve wound healing after cerebral ischemia. In general, this study showed that the clinical effectiveness of baicalin was based on the complementary effects of multiple pathways and networks [ 107 ].…”
Section: Pharmacological Signaling Pathway Network Analysismentioning
confidence: 99%
“…Baicalin activation of the cyclinD-SMAD3-TGF beta network pathway may improve wound healing after cerebral ischemia. In general, this study showed that the clinical effectiveness of baicalin was based on the complementary effects of multiple pathways and networks [ 107 ].…”
Section: Pharmacological Signaling Pathway Network Analysismentioning
confidence: 99%
“…At 24 h after the experimental interventions, the rats were deeply anesthetized, sacrificed by an overdose of anesthesia and quickly treated with a cardiac perfusion of 4% paraformaldehyde. The hippocampi from 3 rats per group were extracted and cut into 12-µm coronal sections with a cryostat (CM 3000; Leica, Manheim, Germany) then placed on glass slides and stored at -80˚C (21,22).…”
Section: Chemicalsmentioning
confidence: 99%
“…The neurons were protected from an excitotoxic injury by inhibiting CaMKII. (Li et al, 2013) aimed to explore any potential correlation between the neuroprotective effects of baicalin on the ischemic area and CaMKII. The protein expression of CaMKII and p-CaMKII was evaluated in gerbils belonging to various treatment groups.…”
Section: Suppressing Ca 2+ Overloadingmentioning
confidence: 99%